G-Protein-Coupled Receptors in Chronic Kidney Disease Induced by Hypertension and Diabetes - Huidi Tang; Kang Li; Zhan Shi; Jichao Wu (Cells)
Hypertension and diabetes are two common causes of chronic kidney disease. Hypertension can induce renal vascular injury, glomerular damage, podocyte loss, and tubular injury, leading to tubulointerstitial fibrosis. A number of factors influence the regulation of hypertension, among which G-protein-coupled receptors (GPCRs) have been studied extensively because they are desirable targets for drug development. Compared to hypertension, the regulatory effects of GPCRs on hypertensive kidney disease (HKD) are less generalized. In this review, we discussed the GPCRs involved in hypertensive kidney disease, such as angiotensin II receptors (AT1R and AT2R), Mas receptor (MasR), Mas-related G-protein-coupled receptor member D (MrgD), relaxin family receptor 1 (RXFP1), adenosine receptors (A1, A2A, A2B, and A3), purinergic P2Y receptors, and endothelin receptors (ETA and ETB). The progression of HKD is rarely reversed but can be retarded by ameliorating the hypertensive microenvironment in the kidneys. However, simply reducing blood pressure cannot stop the progression of HKD. Diabetic nephropathy (DN) is the most common cause of end-stage renal disease (ESRD), which is a major cause of morbidity and mortality in diabetes. Many GPCRs are involved in DN. Here, we select some well-studied GPCRs that are directly associated with the pathogenesis of DN to illustrate their mechanisms. The main purpose of this review is to provide an overview of the GPCRs involved in the occurrence and progression of HKD and DN and their probable pathophysiological mechanisms, which we hope will help in developing new therapeutic strategies.